Integrate thermostabilized fusion protein apocytochrome b562RIL and N-glycosylation mutations: A novel approach to heterologous expression of human UDP-glucuronosyltransferase (UGT) 2B7 - Xue, Jia; Zhang, Haitao; Zeng, Su (Frontiers in Pharmacology, 2022)
Human UDP-glucuronosyltransferase (UGT) 2B7 is a crucial phase II metabolic enzyme that transfers glucuronic acid from UDP-glucuronic acid (UDPGA) to endobiotic and xenobiotic substrates. Biophysical and biochemical investigations of UGT2B7 are hampered by the challenge of the integral membrane protein purification. This study focused on the expression and purification of recombinant UGT2B7 by optimizing the insertion sites for the thermostabilized fusion protein apocytochrome b562RIL (BRIL) and various mutations to improve the protein yields and homogeneity. Preparation of the recombinant proteins with high purity accelerated the measurement of pharmacokinetic parameters of UGT2B7. The dissociation constants (KD) of two classical substrates (zidovudine and androsterone) and two inhibitors (schisanhenol and hesperetin) of UGT2B7 were determined using the surface plasmon resonance spectroscopy (SPR) for the first time. Using negative-staining transmission electron microscopy (TEM), UGT2B7 protein particles were characterized, which could be useful for further exploring its three-dimensional structure. The methods described in this study could be broadly applied to other UGTs and are expected to provide the basis for the exploration of metabolic enzyme kinetics, the mechanisms of drug metabolisms and drug interactions, changes in pharmacokinetics, and pharmacodynamics studies in vitro.